2019
DOI: 10.1002/ped4.12115
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography for guidance in the diagnosis and surgical correction of recurrent pediatric acute dacryocystitis

Abstract: Importance This is the first retrospective study of the effect of computed tomography (CT) in diagnosis and surgical correction of recurrent pediatric acute dacryocystitis (PAD). Objective To explore the pathogenesis of recurrent PAD and the impact of CT in guidance of surgical planning. Methods Medical histories, clinical manifestations, and CT results of 10 patients with recurrent PAD were reviewed. Etiologies and treatment effectiveness were recorded for all patients. Results CT revealed that three patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This suggests the need for adequate ophthalmic evaluations while screening for congenital deformities in patients with PL. CT scans play a crucial role in the diagnosis of congenital nasolacrimal canal dysplasia because it can exactly delineate the shape, direction, and abnormal structure of the bony nasolacrimal duct ( 10 ). Subsidiary MRI and ultrasound exams provided information for planning appropriate management about the mass and assessed the exact location and dimensions of the lacrimal drainage system.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the need for adequate ophthalmic evaluations while screening for congenital deformities in patients with PL. CT scans play a crucial role in the diagnosis of congenital nasolacrimal canal dysplasia because it can exactly delineate the shape, direction, and abnormal structure of the bony nasolacrimal duct ( 10 ). Subsidiary MRI and ultrasound exams provided information for planning appropriate management about the mass and assessed the exact location and dimensions of the lacrimal drainage system.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital dacryocyst is a cyan cystic mass in the inner canthus of newborns, and is caused by obstruction at both ends of the diversion channel [ 6 ]. Some study reported that in children, nearly 60% of patients with congenital dacryocyst eventually develop a peri-dacryocyst infection [ 7 , 8 ]. Dacryocystitis is mainly caused by Gram-positive cocci, especially Streptococcus pneumoniae ; due to the misuse of anti-Gram-positive cocci antibiotics, Gram-negative Enterobacteriaceae have risen in the proportion of dacryocystitis pathogens [ 9 ].…”
Section: Introductionmentioning
confidence: 99%